Strategy Management Analysis in the Face of Business Competition (ADI Journal on Recent Innovation (AJRI), 2023)
This study aimed to examine the influence of cost focus and differentiation focus on business competition. The research adopted a quantitative approach, utilizing questionnaires distributed to a sample of 70 business actors who participated by completing questionnaires. The results support the hypotheses: cost focus positively and significantly affects business competition, as evidenced by a t-value of 3.009. Moreover, cost focus has a significant impact on differentiation focus (t-value: 72.926), while differentiation focus positively influences business competition (t-value: 9.825). The study also finds that cost focus has a significant effect on business competition, mediated by differentiation focus (t-value: 82.751). These findings emphasize the importance of both cost management and differentiation strategies for enhancing business competitiveness.